Giulio Ferroni, Scritture a perdere. Possibilità e responsabilità della critica (ENTHYMEMA, 2010)
The book reviewed in this pages, Giulio Ferroni, Scritture a perdere. La letteratura negli anni zero, Laterza,Bari 2010, deals with the subject which is very important to the author, with a tone  freer, nimble and light than an academic essays. In the one hundred pages of his pamphlet, Ferroni thickens theory and criticism and he is back to speak of short stories and novels with an argument often replaced by interviews, friendly commentaries and celebrations of ordinary craze.